Modeling future sediment retention service in the Bagh-e-Shadi Forest protected area using InVEST and the ACCESS-ESM1-5 climate model - Sharif Joorabian Shooshtari; Tahereh Ardakani; Hadise Beik Khormizi (Scientific Reports)
Abstract Assessing the impact of climate change on water-related ecosystem services (ES) in Protected Areas (PAs) is essential for developing soil and water conservation strategies that promote sustainability and restore ES. However, the application of ES research in Protected Area (PA) management remains ambiguous and has notable shortcomings. This study primarily aimed to assess the SDR-InVEST (Sediment Delivery Ratio-Integrated Valuation of Ecosystem Services and Tradeoffs) model for estimating ES, including soil loss, sediment export, and sediment retention, under various climate change scenarios from 1997 to 2100 in the data-scarce region of the Bagh-e-Shadi Forest PA. Bagh-e-Shadi Forest PA, a forest zone in Yazd Province, Iran, has the highest incidence of fire occurrences, leading to accelerated soil erosion and degradation. Our study is pioneering in the Bagh-e-Shadi Forest for employing the InVEST model, particularly the SDR model, to investigate the effects of climate change on sediment load, soil loss, and sediment retention. Additionally, this study focused on sensitivity analysis to individually assess model parameter uncertainties and highlighted the calibration process. By incorporating the latest IPCC emission scenarios, it addresses a critical research gap in the study area. Sensitivity analyses identified Borselli IC0, forest cover factor, and Borselli k (Kb) as the most influential parameters for sediment export. IC0 and kb are calibration factors that shape the sigmoid function in the SDR–IC relationship. From 1997 to 2021, our findings indicated that the study area experienced an average annual soil loss of 77.1 t ha−1 year−1. Additionally, the average sediment export was 0.08 t ha−1 year−1, while sediment retention averaged 2.2 t ha−1 year−1. The results indicated an increasing impact on ES due to climate change, primarily driven by projected increases in precipitation. Our findings showed that sediment yield export is projected to increase the most under the SSP585 scenario during the period 2041–2060, with a rise of 148.02% compared to baseline conditions. Sediment retention is expected to increase from 25,436.25 t year−1 in the baseline scenario to 63,128.63 t year−1 under SSP585 during the same period. The minimum increase in soil loss is projected to be 40.6% under the SSP126 scenario during the period 2021–2040. The quantified changes in ES provisioning will enhance future land use planning, especially for managing the Bagh-e-Shadi Forest.